Uncertainties in supernova input rates drive qualitative differences in simulations of galaxy evolution - Keller, Benjamin W.; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2022)
ABSTRACT. Feedback from core collapse supernovae (SNe), the final stage of evolution of massive stars, is a key element in galaxy formation theory. The energy b
Gesehen am 07.04.2022